As percepções de professores sobre as influências das masculinidades tóxicas nas vivências pessoais e profissionais - Baptista, Rafael Ferraz (Universidade Federal de São Carlos, 2019)
This research was developed from the perception about how men behave in society, since they need to adapt to the socially established patterns of masculinity and virility, submitting to certain sufferings in order to feel adjusted, a fact that extends to the school environment, considering that it is characterized as an integral part of the society. Therefore, the study aimed to understand teachers' perceptions about the influence of hegemonic patterns of masculinity, identify how teachers deal with the influences of toxic masculinities and understand how the toxicities, derived from the hegemonic pattern, interfer with the experiences of heterosexual teachers and homosexual teachers. Thus, we define the following research question: What are the teachers' perceptions about the influences of toxic masculinities in the construction of their identities? How do the values of a hegemonic pattern of masculinity interfere in the formation of these individuals as men and teachers? The data collection that supported this research was performed with the aid of two collection instruments: participant-observation and, especially, the operative group. Pichon Rivière (2005) emphasizes that the creation of an operative group allows a discussion that leads participants to reflect about certain theme, in this case, about the influence of toxic masculinities in the personal and professional lives of male teachers. Thus, seven male teachers from the state public school system participated in this research, sharing knowledge, yearnings and feelings during the debates. The debates generated the discourses that supported the research results, which, through content analysis (BARDIN, 2011), allowed us to find that toxic masculinities contaminate and condition the formation of man, putting him in a situation of subordination in relation to hegemonic masculinity and consequently its values are reproduced in the school environment, reinforcing toxic relationships, leading to practices lacking affection and based on fear and authoritarianism. In addition, teachers' perceptions indicate a certain uneasiness, which led to the questioning of the segregating, coercive and oppressive practices arising from hegemonic masculinity, which cause suffering and hindering the formation of man as a human being.
Teacher's perceptions about the influences of toxic masculinities in personal experience and professionals
Keywords: Masculinidade hegemônica; Docência masculina; Docência e masculinidades.; Teaching and masculinities; Male teaching; Hegemonic masculinity; CIENCIAS HUMANAS